Urgensi Pendidikan Politik dalam Islam - Husni Mubarak (Al-Widad, 2024)
Ideally, political education in Islam serves as a means to develop the political awareness of the Muslim community based on the values of justice, trustworthiness, and social responsibility, so that politics is understood as a form of service aimed at achieving public welfare. However, in reality, Islamic political education has not been implemented optimally, as indicated by the low level of political literacy, the prevalence of political pragmatism, and the tendency to separate Islamic values from political practices. This condition has resulted in a gap between the ideal teachings of Islam and the reality of contemporary political life. This study aims to examine the urgency of political education in Islam and its role in shaping political awareness and ethical political behavior among Muslims. The research employs a library-based study with a qualitative approach, using descriptive-analytical methods to examine primary sources such as the Qur’an and Hadith, as well as secondary sources including scholarly books and academic journal articles. The findings indicate that political education in Islam plays a strategic role in integrating moral and spiritual values into political life and offers a solution to the ethical crisis and low political awareness within the Muslim community.